PENGARUH INTERAKSI SOSIAL TEMAN SEBAYA TERHADAP KARAKTER CINTA DAMAI SISWA KELAS IV DI SDN KEDOYA UTARA 04 - Fitria Rosmi; Ismiatul Hasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The decline in the quality of social interaction among elementary school students has become a critical issue in education. Many students tend to display individualistic behavior, form exclusive groups, and even engage in verbal or physical aggression toward peers. This reflects a weak peace-loving character that should ideally develop from an early age within the school environment. A lack of tolerance, empathy, and skills in resolving conflicts peacefully hinders the creation of a harmonious learning atmosphere. This study aims to examine the influence of peer social interaction on the peace-loving character of fourth-grade students at SDN Kedoya Utara 04. A quantitative approach with a survey method was employed. The research sample consisted of 64 students selected through a saturated sampling technique. The research instrument was a Likert-scale questionnaire, with the independent variable (X) — peer social interaction — covering aspects of communication, attitudes, and group behavior, and the dependent variable (Y) — peace-loving character — including mutual trust, tolerance, and cooperation. Simple linear regression analysis revealed a significant influence of peer social interaction on peace-loving character, with an F-value of 73.894 and a significance level of 0.000 < 0.05. The coefficient of determination (r²) was 0.544, indicating that peer social interaction contributed 54.4% to the development of peace-loving character, while the remaining 45.6% was influenced by other factors. These findings highlight the importance of prioritizing positive social interaction in elementary school character education.